Dieta de um grupo de muriquis-do-norte Brachyteles hypoxanthus (Kuhl, 1820) (Primates, Atelidae) em um fragmento florestal de Santa Maria de Jetibá, ES, Brasil. - Machado, Flávia Figueiredo (2012)
The northern muriqui (Brachyteles hypoxanthus) is an endemic primate to the Atlantic Forest in Espírito Santo (ES) and Minas Gerais (MG), Brazil, critically endangered. Their diet is based on fruits and leaves, but they also consume flowers and buds. The feeding strategies of muriquis are determined by environmental variables, proprieties and availability of resources and intrinsic variables of each population. This can generate intra and inter population differences. This study aimed to investigate the proportion of use of the items, feeding resources and plant species by a group of 18 muriquis, as well as the variations in consumption between two distinct bioclimatic stations. The group studied was monitored from January to December 2006 (except July) in a forest fragment of 70 ha of Santa Maria de Jetibá, ES (SMJ), through scan sampling. Muriquis devoted an average of 20% of their daily activity in feeding. Leaves were the most representative in the diet (34.04%), but this consumption was proportionally lower than that observed in other studies. Buds (17.94%) and flowers (21.37%) presented high consumption, not observed in groups of other sites. There was no significant difference in the consumption of fruits (22.35%), flowers and buds. Only the consumption of flowers and fruits changed between bioclimatic stations. Flowers were more consumed in the rainy season and fruits in the dry season. In the period with higher consumption of fruits, the immature ones were the most consumed. Probably, those cases occurred because the restrict size of the fragment, so there isn’t large supply of edible fruits, necessitating the use of less energy items, such as flowers, immature fruits and buds. Immature leaves were more consumed than mature ones in the rainy season, a period with great offer this item due to leaf growth and replacement. Trees were the most commonly used feeding resources. Both male and female showed no significant differences in the proportion of consumption of the items and time spent on feeding. There were identified 44 plants species on the diet of the group studied. Only five species were consumed at both stations: Tibouchina arborea, Tovomita brasiliensis,Terminalia sp., Vochysia saldanhanam e Virola oleifera. The tree species V. oleifera, Ocotea aciphylla, Hirtella martiana, Micropholis sp., Terminalia sp., H.hebeclada, O. glaziovii e V. saldanhanam represented more than 50% of feeding records in any of the periods analyzed. Because of the high consumption of these species, they should be considered in conservations programs aimed at the conservation of muriquis in SMJ